1980
DOI: 10.1017/s0043174500055557
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Row Spacing on Competitiveness and Yield of Peanuts (Arachis hypogaea)

Abstract: Peanuts [Arachis hypogaea(L.) ‘Florunner’], infested with sicklepod (Cassia obtusifoliaL.) and Florida beggarweed [Desmodium tortuosum(Sw.) DC.] were grown in 20.3-, 40.6-, and 81.2-cm rows on Dothan sandy loam at Headland, Alabama, and on Greenville sandy clay loam at Plains, Georgia. In-row seeding rates were equal, regardless of row width. Peanuts were maintained free of sicklepod and Florida beggarweed for 0, 2, and 5 weeks after emergence or throughout the season. In either the absence or presence of weed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…Johnson et al (2005) found that total weed densities were less when peanut rows were spaced 30 cm apart compared with rows spaced 91 cm apart. Similar results were obtained by Buchanan and Hauser (1980). Late-season control of Florida beggarweed, sicklepod (Senna obtusifolia L.), and Texas millet [Urochloa texana (Buckl.)…”
supporting
confidence: 80%
“…Johnson et al (2005) found that total weed densities were less when peanut rows were spaced 30 cm apart compared with rows spaced 91 cm apart. Similar results were obtained by Buchanan and Hauser (1980). Late-season control of Florida beggarweed, sicklepod (Senna obtusifolia L.), and Texas millet [Urochloa texana (Buckl.)…”
supporting
confidence: 80%
“…If the crop was distributed in a perfectly uniform pattern, crop plants would begin competing with weed plants sooner, while the crop still had its size advantage, whereas competition among crop plants would be delayed as long as possible (Fisher & Miles 1973). This prediction is supported by studies showing that decreased row spacing, which reduces the degree of ‘clumping’, usually results in a modest reduction in yield losses due to weeds (Buchanan & Hauser 1980; Patterson et al . 1988; Smith et al .…”
Section: Introductionmentioning
confidence: 75%
“…For example, increased seeding rates and decreased row spacing increase crop resource uptake under weed-infested conditions by increasing crop biomass early in growth (Walker andBuchanan 1982, Minotti 1990). Marked decreases in weed growth in narrow (~20 em) vs. wide (~75 em) row spacing have been observed in many major crops, e.g., 55 and 37% in peanut (Arachis hypogaea L.; Buchanan and Hauser 1980) and grain sorghum (Wiese et al 1964), respectively. However, extremely narrow row spacing may prevent cultivation operations important to control of certain weeds (Martinet al 1977).…”
Section: Increasing Crop Interference By Crop Managementmentioning
confidence: 99%